Network Geeks How They Built the Internet - Carpenter, Brian E.; SpringerLink (Online service) (London : Springer London : Imprint: Copernicus, 2013)
The impact on modern society made by the Internet is immeasurable. Yet some questioned (3z(Bwhy anyone would want such a thing(3y (Bwhen the idea was first introduced. Part history, part memoir and part cultural study, Network Geeks charts the creation of the Internet and the establishment of the Internet Engineering Task Force, from the viewpoint of a self-proclaimed geek who witnessed these developments first-hand. With boundless enthusiasm and abundant humour, Brian Carpenter leads the reader on a journey from post-war Britain to post-millennium New Zealand, describing how the Internet grew into today$1 (Bs ubiquitous, global network, including the genesis of the World-Wide Web in the hotbeds of a particle collider at CERN. Illuminating the science and technology behind the apparent (3z(Bmagic trick(3y (Bof the Internet, Network Geeks opens a window into the initially bewildering world of the Internet engineering geek. After reading this book, you may wish to join this world yourself.s
Hey Folks! -- Before My Time -- Where Do Geeks Come From? -- Going Up -- In Control -- Two Ivory Towers -- Diversity -- Economy Class -- Parallel Universes -- The Years of Miraculous Growth -- Going Under.
Keywords: Computer science; Mathematics; Computer Science; History of Computing; Popular Science in Mathematics/Computer Science/Natural Science/Technology.; Information Systems Applications (incl. Internet).